Oil Wealth, Weak Institutions, and Governance Risk in Emerging Petro-States - Paul (Sr.), tanley Anthony Vivion; Joseph, Justin; Paul (Jr.), Stanley Anthony Vivion; Solomon, Orande Kenneatior (Stallion Journal for Multidisciplinary Associated Research Studies, 2026)
This article argues that the central governance problem in emerging petro-states is not the presence of oil wealth itself, but the interaction between sudden revenue expectations and weak institutional restraint. Where licensing systems are opaque, fiscal rules underdeveloped, and accountability institutions politically vulnerable, petroleum wealth can magnify rather than solve development deficits. Drawing on resource-governance evidence and classic scholarship on the political economy of oil, the article contends that new producers face a narrow window in which to establish credible rules before rent expectations harden into entitlement politics. The most serious risks lie in discretionary licensing, off-budget spending, weak parliamentary oversight, and the politicization of state-owned enterprises. The article concludes that institutional sequencingnot merely production volume, determines whether oil becomes a developmental instrument or a governance accelerant for fragility.